Overcoming immunosuppression in cancer: how ketogenic diets boost immune checkpoint blockade - Victoria E. Stefan; Daniela D. Weber; Roland Lang; Barbara Kofler (Cancer Immunology, Immunotherapy)
Abstract Immune checkpoint blockade (ICB) is now part of the standard of care in the treatment of many forms of cancer, yet it lacks efficacy in some patients, necessitating adjunct therapies to support the anti-tumor immune response. Ketogenic diets (KDs), i.e., high-fat low-carbohydrate diets, have been shown to have antiproliferative and immunomodulatory effects in various preclinical cancer studies. Here, we review current knowledge of the complex interplay of KDs and the anti-tumor immune response in the context of ICB therapy, to update our understanding of diet-induced immunometabolic reprogramming in cancer. Preclinical cancer studies have revealed increased activation of and infiltration by tumor-fighting immune cells, especially CD8+ T cells, but also M1 macrophages and natural killer cells, in response to a KD regimen. In contrast, immune-suppressive cells such as regulatory CD4+ T lymphocytes, M2 macrophages, and myeloid-derived suppressor cells were reported to be decreased or largely unaffected in tumors of KD-fed mice. KDs also showed synergism with ICB therapy in several preclinical tumor studies. The observed effects are ascribed to the ability of KDs to improve immune cell infiltration and induce downregulation of immune-inhibitory processes, thus creating a more immunogenic tumor microenvironment. The studies reviewed herein show that altering the metabolic composition of the tumor microenvironment by a KD can boost the anti-tumor immune response and diminish even immunotherapy-resistant as well as immunologically "cold" tumors. However, the exact underlying mechanisms remain to be elucidated, requiring further studies before KDs can be successfully implemented as an adjunct tumor therapy to improve survival rates for cancer patients.